Nurse-led clinic for patients with liver cirrhosis—effects on health-related quality of life: study protocol of a pragmatic multicentre randomised controlled trial - Anncarin Svanberg; Maria Hjorth; Daniel Sjöberg; Elenor Kaminsky; Sophie Langenskiöld; Fredrik Rorsman (BMJ Open)
Introduction Liver cirrhosis affects health-related quality of life (HRQoL) even in its early stages. Morbidity is especially high when the disease decompensates and self-care actions become essential. Nurse involvement in secondary prevention in other chronic diseases has contributed to better symptom control, less need of inpatient care and improved HRQoL. In order to evaluate the impact of nurse involvement in the follow-up of patients with liver cirrhosis, we decided to compare structured nurse-led clinics, inspired by Dorothea Orem’s nursing theory and motivational strategies, with a group of patients receiving standard care. The primary outcome is HRQoL and the secondary outcomes are quality of care, visits to outpatient clinics or hospitals, disease progress and health literacy.Methods and analysis This is a pragmatic, multicentre randomised controlled study conducted at six Swedish hepatology departments. Eligible patients are adults with diagnosed cirrhosis of the liver (n=500). Participants are randomised into either an intervention with nurse-led follow-up group or into a standard of care group. Recruitment started in November 2016 and is expected to proceed until 2020. Primary outcomes are physical and mental HRQoL measured by RAND-36 at enrolment, after 1 and 2 years.Ethics and dissemination The study is ethically approved by the Regional Ethical Review Board in Uppsala. The results shall be disseminated in international conferences and peer-reviewed articles.Trial registration number NCT02957253; Pre-results.